Evidence of a Recessively Inherited CCN3 Mutation as a Rare Cause of Early-Onset Parkinsonism - Bentley, Steven R.; Khan, Suliman; Öchsner, Marco; Premarathne, Susitha; Aslam, Zain; Fowdar, Javed Y.; Iqbal, Jamila; Naeem, Muhammad; Love, Christopher A.; Wood, Stephen A.; Mellick, George D.; Sykes, Alex M. (Frontiers in Neurology, 2020)
The study of consanguineous families has provided novel insights into genetic causes of monogenic parkinsonism. Here we present a family from the rural Khyber Pakhtunkhwa province, Pakistan, where three siblings were diagnosed with early-onset parkinsonism. Homozygosity mapping of two affected siblings and three unaffected family members identified two candidate autozygous loci segregating with disease, 8q24.12-8q24.13 and 9q31.2-q33.1. Whole exome sequence analysis identified a single rare homozygous missense sequence variant within this region, CCN3 p.D82G. Although unaffected family members were heterozygous for this putative causal mutation, it was absent in 3,222 non-PD subjects of Pakistani heritage. Screening of 353 Australian PD cases, including 104 early-onset cases and 57 probands from multi-incident families, also did not identify additional carriers. Overexpression of wildtype and the variant CCN3 constructs in HEK293T cells identified an impaired section of the variant protein, alluding to potential mechanisms for disease. Further, qPCR analysis complemented previous microarray data suggesting mRNA expression of CCN3 was downregulated in unrelated sporadic PD cases when compared to unaffected subjects. These data indicate a role for CCN3 in parkinsonism, both in this family as well as sporadic PD cases, however, the specific mechanisms require further investigation. Additionally, further screening of the rural community where the family resided is warranted to assess the local frequency of the variant. Overall, this study highlights the value of investigating under-represented and isolated affected families for novel putative parkinsonism genes.